Effect of Health Service Quality Toward Patients Satisfaction - Jeny Riska Vatica; Nur’aini Nur’aini; Masnelly Lubis (Journal La Medihealtico, 2021)
The quality of service at the Community Health Center (Puskesmas) is an important factor in creating patient satisfaction. The results of measuring patient satisfaction that are objective and accurate can assist the health center in formulating a better form of service. The purpose of this study was to determine and analyze the effect of health service quality on outpatient satisfaction. This type of research is an analytic survey with a cross sectional approach using primary data with questionnaires and secondary data from Community Health Center (Puskesmas) reports. The population in this study were patients who had outpatient visits from January to July 2020 with a total sample of 99 people who were determined using the accidental sampling method. The analysis used univariate, bivariate and multivariate analysis. Chi square test results showed that technical competence (p = 0.001 <0.05), effectiveness (p = 0.002 <0.05), human relations (p = 0.000 <0.05), comfort (p = 0.099> 0, 05) and timeliness (p = 0.001 <0.05). The logistic regression test shows that the variable that most influences patient satisfaction is the relationship between humans with an Exp (B) value of 4.195. The conclusion of this research is that technical competence, effectiveness, human relations and timeliness have a relationship with patient satisfaction, while comfort has no relationship with patient satisfaction. Efforts are needed to improve the quality of outpatient services by establishing a harmonious relationship between health workers and patients in order to achieve services that are able to satisfy patients.